New species and records of Colombian, Ecuadorian and Venezuelan Anacroneuria (Plecoptera: Perlidae), with a review of the Anacroneuria aymara Stark & Sivec Complex - Stark, Bill P. (Illiesia, 2014)
Neaviperla forcipata is figured as line drawings and scanning electron micrographs and reasons are given why Neaviperla Ricker 1943 should be a separate genus rather than a synonym of the genus Suwallia Ricker 1943.
Keywords: entomology; stoneflies; Perlidae; Plecoptera; Anacroneuria; new species; Colombia; new records; Ecuador; Venezuela